Data Mining and Analysis : Fundamental, Concepts and Algorithms - Birant, Derya, ontributors; Su, Ying, ontributors; Li, Jing-song, ontributors; Yu, Hai-yan, ontributors; Zhang, Xiao-guang, ontributors; Simunek, M., ontributors; Rauch, J., ontributors; Santos, Henrique, ontributors; Santos, Filipe Manuel, ontributors; Mathew, Wesley, ontributors; Lamirel, Jean-Charles, ontributors; Kouamou, Georges Edouard, ontributors; et al. (United Kingdom : Koros Press Limited, 2017)
Includes bibliographical references